Determination of cognitive development: postnonclassical theoretical model - Irina N. Pogozhina (Национальный психологический журнал, 2015)
The aim of this research is to develop a postnonclassical cognitive processes content determination model in which mental processes are considered as open selfdeveloping, self-organizing systems. Three types of systems (dynamic, statistical, developing) were analysed and compared on the basis of the description of the external and internal characteristics of causation, types of causal chains (dependent, independent) and their interactions, as well as the nature of the relationship between the elements of the system (hard, probabilistic, mixed). Mechanisms of open non-equilibrium nonlinear systems (dissipative) and four dissipative structures emergence conditions are described. Determination models of mental and behaviour formation and development that were developed under various theoretical approaches (associationism, behaviorism, gestaltism, psychology of intelligence by Piaget, Vygotsky culture historical approach, activity approach and others) are mapped on each other as the models that describe behaviour of the three system types mentioned above. The development models of the mental sphere are shown to be different by the following criteria: 1) allocated determinants amount; 2) presence or absence of the system own activity that results in selecting the model not only external, but also internal determinants; 3) types of causal chains (dependent-independent-blended); 4) types of relationships between the causal chain that ultimately determines the subsequent system determination type as decisive (a tough dynamic pattern) or stochastic (statistical regularity). The continuity of postnonclassical, classical and non-classical models of mental development determination are described. The process of gradual refinement, complexity, «absorption» of the mental determination by the latter models is characterized. The human mental can be deemed as the functioning of the open developing non-equilibrium nonlinear system (dissipative). The mental sphere is described as a self-organizing system with six common features of self-organizing systems. Three general and three local demands for the development of postnonclassical determination development model of cognitive structures were defined. It is concluded that postnonclassical cognitive structures formation and development model and its application to a specific substantive material should contain a description of the three groups of factors: 1) self-development trends in the cognitive structure as an integrated system; 2) configuration and methods of effects on the cognitive structure functioning and development from the outside (external determination); 3) mechanisms of the external factors influence on the development of cognitive structures. By studying and describing these factors, it will be possible to transfer the link between learning and development from the stage of theoretical analysis to the level of applied technology. This technology allows to influence on the cognitive systems development and also increase its efficacy by external determinants influence (generative cause) on the cognitive structures self-organization mechanisms (internal determinants) according to the potentialities of its self-development.